The Existence of the Protestant Church in Western Indonesia (GPIB) as a Reflection of Religious Tolerance in Banda Aceh City - Syukrullah Syukrullah; Mawardi Mawardi; Nurlaila Nurlaila (Muqaranah Al-Adyan: Multidisciplinary Perspective on Religions, 2025)
This study aims to analyze the existence of the Protestant Church in Western Indonesia (GPIB) in Banda Aceh City as a reflection of religious tolerance within a predominantly Muslim society. The research is grounded in the socio-religious dynamics of Banda Aceh, a region implementing Islamic law while guaranteeing freedom of religion for other faith communities. A qualitative descriptive approach was employed through in-depth interviews, field observations, and document analysis. The findings indicate that the presence of GPIB is socially accepted due to effective communication between the church congregation, local community leaders, and the government. Factors supporting this tolerance include local cultural values, inclusive regional policies, and the role of religious figures in maintaining harmony. Therefore, the existence of GPIB in Banda Aceh represents a dynamic form of tolerance that balances religious identity and local governance.